2024
DOI: 10.1037/trm0000419
|View full text |Cite
|
Sign up to set email alerts
|

Work-related trauma exposure: Influence on child welfare workers’ mental health and commitment to the field.

Abstract: The field of child welfare continues to be plagued by high rates of worker turnover that further complicate the challenging work of protecting and enhancing child welfare in the United States. The child welfare workforce plays a crucial role in promoting child well-being and preventing abuse and neglect, but safety, permanence, and well-being outcomes of children are negatively impacted by high rates of workers leaving their jobs. Numerous organizational and individual factors have been studied in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…One possible explanation for this underreporting could be that those exposed, consciously or unconsciously, find it threatening to their self-esteem to label themselves as victims ( Nielsen et al, 2010 ). Other possible explanations could include the stigma child welfare workers feel related to being a victim or an underlying fear of being blamed for the incident ( King, 2019 ). Moreover, given that workplace violence is deemed to be an inevitable part of their job ( Lamothe et al, 2018 ), the threshold child welfare workers have for perceiving and reporting something as actual violence might be considerably higher compared to workers in other sectors in which workplace violence is not a prominent issue (e.g., within construction or finance).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this underreporting could be that those exposed, consciously or unconsciously, find it threatening to their self-esteem to label themselves as victims ( Nielsen et al, 2010 ). Other possible explanations could include the stigma child welfare workers feel related to being a victim or an underlying fear of being blamed for the incident ( King, 2019 ). Moreover, given that workplace violence is deemed to be an inevitable part of their job ( Lamothe et al, 2018 ), the threshold child welfare workers have for perceiving and reporting something as actual violence might be considerably higher compared to workers in other sectors in which workplace violence is not a prominent issue (e.g., within construction or finance).…”
Section: Discussionmentioning
confidence: 99%
“…Combined, having this mindset may increase the employees’ threshold for labeling these aggressive acts as violent incidents. Additionally, child welfare workers might hesitate to label aggressive acts as violent incidents due to the stigma related to being a victim, as well as an underlying fear of being blamed for the incident ( King, 2019 ; Munobwa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While these job functions are essential for enhancing child safety, permanency, and well-being, these can be emotionally challenging and result in a higher level of STS. Many studies have shown that STS harms child welfare workers’ health, well-being, high-quality services, and retention (Caringi & Hardiman, 2011; King, 2022; Rienks, 2020). Furthermore, child welfare workers’ STS can lead to long-term negative consequences for children and families with whom they work together, including decreasing their safety, permanency, and well-being (Denne et al, 2019; Hensel et al, 2015).…”
Section: Organizational Justice and Stsmentioning
confidence: 99%